Event-Driven Edge Agent Framework for Distributed Control in Distribution Networks - Xianglong Zhang; Ying Liu; Songlin Gu; Yuzhou Tian; Yifan Gao (Energies)
With the large-scale integration of heterogeneous energy resources and the increasing demand for flexible control, centralized control is facing challenges in terms of operational efficiency and system responsiveness when handling high-precision regulation tasks. To address this issue, this paper proposes an event-driven edge agent framework for distributed control in power distribution networks. First, based on the diverse requirements of distributed control in distribution networks, an edge agent architecture is constructed with modular components such as configuration management at its core. Second, considering the hybrid system characteristics of distribution networks, a control configuration technique based on activity-on-edge is designed, which decouples and discretizes continuous control processes through event-driven mechanisms. Furthermore, an edge-oriented automatic differentiation solver and a lightweight web application framework are developed to address the challenges of real-time optimization under resource-constrained environments. Finally, a semi-physical simulation is conducted using station-level economic dispatch as a case study to verify the effectiveness of the proposed technology. The results demonstrate that, compared to centralized control, the designed distributed agent maintains optimization accuracy while reducing event-triggering frequency by 40% and improving communication response speed by 70%, showing strong performance in operational efficiency at the edge.